Helping the struggling adolescent : a guide to thirty-five common problems for counselors, pastors, and youth workers - Parrott, Les. (Grand Rapids, Mich. : Zondervan Publishing House, 2000)
Publisher's description: Helping the Struggling Adolescent is your first resource to turn to when a teen you know is in trouble. Whether you're a youth worker, counselor, pastor, or teacher, this fast, ready reference is a compendium of insight on teen problems from abuse to violence and everything between. Help starts here for thirty-six common, critical concerns. Topics are arranged in alphabetical order. Each chapter gives you essential information for several vital questions: What does the specific struggle look like? Why did it happen? How can you help? When should you refer to another expert? Where can you find additional resources? Arranged in three sections, this book first gives you the basics of being an effective helper, Then it informs you on the different struggles of adolescents. The final section--a key component of this book--supplies more than forty rapid assessment tools for use with specific problems. Helping the Struggling Adolescent organizes and condenses biblical counseling issues for teens into one extremely useful volume. Keep it in arm's reach for the answers you need, right when you need them.
PART 3. Rapid assessment tools. Using and interpreting rapid assessment tools -- Anger situations form -- Are you dying to be thin? -- Attitudes toward cohabitation questionnaire -- Bulimia test checklist for making a major decision -- Child's attitude toward father -- Child's attitude toward mother -- Clinical anxiety scale -- Cognitive slippage scale -- Compulsive eating scale -- Compulsiveness inventory -- Concern over weight and dieting scale -- Dysfunctional attitude scale -- Eating attitudes test -- Family adaptability and cohesion evaluation scale -- Fear questionnaire -- Fear survey schedule, II -- Generalized contentment scale -- Goldfarb fear of fat scale -- Guilt scale -- Hare self-esteem scale -- Index of self-esteem -- Intense ambivalence scale -- Internal versus external control of weight scale -- Internet addiction test -- Inventory of religious belief -- Michigan alcoholism screening test -- Mobility inventory for agoraphobia -- Novaco anger scale -- Obsessive-compulsive scale -- Reasons for living inventory -- Restraint scale -- Revised UCLA loneliness scale -- Self-efficacy scale -- Self-rating anxiety scale -- Self-rating depression scale -- Skills for classroom success checklist -- Skills for study success checklist -- Stanford shyness survey -- State-trait anger scale -- Stressors rating scale -- Teen alert questionnaire --Tough turf peer pressure quiz -- List of rapid assessment instruments cross-referenced by problem area -- Biblical guidance for struggling adolescents -- Helpful Web sites -- Index.
"With 43 assessment tests!"--Cover.
Includes bibliographical references and index.
Keywords: Teenagers -- Counseling of -- United States; Church work with teenagers -- United States; Adolescent psychology -- United States